2019
DOI: 10.1111/ans.15363
|View full text |Cite
|
Sign up to set email alerts
|

Change in serum albumin level predicts short‐term complications in patients with normal preoperative serum albumin after gastrectomy of gastric cancer

Abstract: Background The purpose of this study was to evaluate the correlation between serum albumin level change (ΔALB) and post‐operative complications in patients with normal preoperative serum albumin after gastrectomy of gastric cancer. Methods A total of 193 patients undergoing curative (R0) gastrectomy from September 2015 to May 2017 were enrolled in this study. The risk factors for predicting post‐operative complications were identified by univariate and multivariate analysis. The cut‐off value and diagnostic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Ai et al found that in patients with normal preoperative albumin level and gastric cancer, ΔAlb was associated with postoperative complications (OR 14, 95% CI 6–32) (Ai et al, 2019 ). The authors found a discriminative threshold of relative ΔAlb on POD 1 at 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Ai et al found that in patients with normal preoperative albumin level and gastric cancer, ΔAlb was associated with postoperative complications (OR 14, 95% CI 6–32) (Ai et al, 2019 ). The authors found a discriminative threshold of relative ΔAlb on POD 1 at 19%.…”
Section: Resultsmentioning
confidence: 99%
“…Studies of albumin and AGR in GC patients are mostly related to survival, and there are few studies which have examined the relationships of albumin and AGR with the risk of postoperative complications. Ai et al (10) stated that the rate of decrease in albumin values on the first day after surgery in GC patients may be a predictive factor for the risk of postoperative complications. In the current study, a statistically significant relationship was found between low AGR and length of stay in ICU, serious postoperative complications, anastomotic leakage, and in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Globulin, which constitutes two main components of serum proteins and contains albumin and inflammatory cytokines, which are generally indicators of nutritional status, plays an important role in cancer immunity and prognosis (7). Studies have been conducted on the albumin to globulin ratio (AGR), some of which have included only albumin to predict survival in various types of cancer and others which more recently have evaluated albumin and globulin together (8)(9)(10). There are only a few studies in the literature that have examined the relationship between AGR rate and GAC, in terms of severe postoperative complications, early mortality and TNM staging.…”
Section: Albümin-globulin Oranı Mide Kanseri Hastalarında Kısa Dönem Komplikasyonları öNgörür Mü?mentioning
confidence: 99%
“…Decreases of 14 and 19% in cut-off values for ALB have been suggested for recognizing patients at a high risk for complications after gastric cancer resection [ 9 , 10 ]. The role of albumin as an independent prognostic marker in ovarian tumors is debated [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%